Vitamin D Deficiency in Pediatric Critical Care - McNally, J. Dayre (J Pediatr Intensive Care, 2016)
Vitamin D deficiency (VDD) is a well-established cause of pediatric bone and muscle disease. In addition, a role has been recognized for vitamin D in the health and stress response of other organs, including the cardiovascular, immune, and respiratory systems. As these organs are central to the development of and recovery from critical illness, VDD has been hypothesized to be a modifiable risk factor for ICU outcome. Over the past 5 years, a growing number of adult and pediatric critical care studies have investigated the prevalence of VDD and its association with illness severity and outcome. The adult studies have recently been synthesized in systematic reviews, with results that convincingly suggest the need for trials to determine whether optimization of vitamin D status improves outcome. In contrast, the pediatric ICU and related literature has not been similarly synthesized. The goal of this review is to describe vitamin D metabolism, known biological mechanisms, potential role in pathophysiology, and summarize the available pediatric intensive care unit (PICU) studies reporting on prevalence of VDD deficiency and its association with outcome. The problems with currently approved supplementation approaches and alternative strategies are discussed, including evidence from available RCTs in adult ICU. Altogether the results suggest that critically ill children are at risk for VDD, and that VDD appears to be associated with a worse clinical course. Clinical trials evaluating novel approaches to testing for and supplementing vitamin D require exploration.